2021
DOI: 10.3389/fphar.2021.629561
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Platform Metabolomics Analyses Revealed the Complexity of Serum Metabolites in LPS-Induced Neuroinflammed Rats Treated with Clinacanthus nutans Aqueous Extract

Abstract: The use of metabolomics as a comprehensive tool in the analysis of metabolic profiles in disease progression and therapeutic intervention is rapidly advancing. Yet, a single analytical platform could not be applied to cover the entire spectrum of a biological sample’s metabolome. In the present paper, multi-platform metabolomics approaches were explored to determine the diverse rat sera metabolites extracted from intracerebroventricular lipopolysaccharides (LPS)-induced neuroinflammed rats treated with oral th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…In the present study we identified 182 DAMs belonging to lipids and lipid-like molecules. Also, phosphatidylcholine (PC), phosphatidylethanolamine (PE), arachidonic acid, prostaglandin I2 and lecithin were significantly altered in the LPS group in the present study, and our results are consistent with previous studies ( Ahmad Azam et al, 2021 ; Gao et al, 2021 ). Combined analysis showed that the “PPAR signalling pathway,” “phosphatidylinositol metabolism,” and “phosphatidylinositol signaling system” are important metabolic pathways in the jejunum.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study we identified 182 DAMs belonging to lipids and lipid-like molecules. Also, phosphatidylcholine (PC), phosphatidylethanolamine (PE), arachidonic acid, prostaglandin I2 and lecithin were significantly altered in the LPS group in the present study, and our results are consistent with previous studies ( Ahmad Azam et al, 2021 ; Gao et al, 2021 ). Combined analysis showed that the “PPAR signalling pathway,” “phosphatidylinositol metabolism,” and “phosphatidylinositol signaling system” are important metabolic pathways in the jejunum.…”
Section: Discussionsupporting
confidence: 94%